HOW ENGLISH PROFICIENCY ENHANCES CROSS-CULTURAL COMMUNICATION IN THE GLOBAL GREEN ECONOMY (KIUT Publication, 2025)
The global green economy seeks to promote sustainability, use renewable energy and champion environmentally friendly approaches. As businesses and governments collaborate across boarders to address climate change, effective communication becomes essential. English, as the dominant lingua franca, plays a pivotal role in facilitating cross-cultural interactions in this sector. This paper discusses how understanding English helps people in the green economy by encouraging teamwork, preventing confusion and making important information available to them. The findings suggest that having good language skills helps individuals and companies to succeed in making sustainability decisions globally and locally. It is found that better English language abilities can help greatly in achieving global green goals.